Altered expression of vesicular glutamate transporter-2 and cleaved caspase-3 in the locus coeruleus of nerve-injured rats - Bravo, Lidia; Mariscal, Patricia; Llorca-Torralba, Meritxell; López-Cepero, Jose María; Nacher, Juan; Berrocoso, Esther (Frontiers in Molecular Neuroscience, 2022)
Neuropathic pain is a debilitating chronic condition provoked by a lesion in the nervous system and it induces functional alterations to the noradrenergic locus coeruleus (LC), affecting distinct dimensions of pain, like sensorial hypersensitivity, pain-induced depression, and anxiety. However, the neurobiological changes induced by nerve damage in the LC remain unclear. Here, we analyzed excitatory and inhibitory inputs to the LC, as well as the possible damage that noradrenergic neurons suffer after the induction of neuropathic pain through chronic constriction injury (CCI). Neuropathic pain was induced in male Sprague-Dawley rats, and the expression of the vesicular glutamate transporter 1 or 2 (VGLUT1 or VGLUT2), vesicular GABA transporter (VGAT), and cleaved caspase-3 (CC3) was analyzed by immunofluorescence 7 (CCI7d) or 28 days after the original lesion (CCI28d). While no significant differences in the density of VGLUT1 puncta were evident, CCI7d induced a significant increase in the perisomatic VGLUT2/VGAT ratio relative to Sham-operated and CCI28d animals. By contrast, when the entire region of LC is evaluated, there was a significant reduction in the density of VGLUT2 puncta in CCI28d animals, without changes in VGLUT2/VGAT ratio relative to the CCI7d animals. Additionally, changes in the noradrenergic soma size, and a lower density of mitochondria and lysosomes were evident in CCI28d animals. Interestingly, enhanced expression of the apoptotic marker CC3 was also evident in the CCI28d rats, mainly co-localizing with glial fibrillary acidic protein but not with any neuronal or noradrenergic marker. Overall, short-term pain appears to lead to an increase of markers of excitatory synapses in the perisomatic region of noradrenergic cells in the LC, an effect that is lost after long-term pain, which appears to activate apoptosis.